Enhancing Children's Creativity Through Ecoprint Activities in Arts Learning at Pembina Tamban Baru State Kindergarten - Maslihat Maslihat; Noor Baiti; Muhammad Zulkarnaen (CV. Edujavare Publishing, 2026)
Creativity is one of the essential competencies that should be developed in early childhood because it supports children's ability to think imaginatively, solve problems, and express ideas through meaningful learning experiences. This study aimed to improve children's creativity through the implementation of ecoprint activities in arts learning. The research employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart model, consisting of two cycles with four stages: planning, action, observation, and reflection. The participants were 15 children in Group B. Data were collected through observation, interviews, and documentation and analyzed using descriptive quantitative and qualitative techniques. The findings demonstrated a continuous improvement in children's creativity throughout the intervention. Creativity achievement increased from 25.00% in the pre-cycle to 31.67% in Cycle I Meeting I, 60.48% in Cycle I Meeting II, 65.95% in Cycle II Meeting I, and finally 82.38% in Cycle II Meeting II, exceeding the predetermined success criterion of 75%. Overall, children's creativity improved by 57.38 percentage points. The findings indicate that ecoprint-based arts learning effectively promotes children's creativity by encouraging exploration, imagination, originality, and active participation through direct interaction with natural materials. Therefore, ecoprint can be considered an innovative and environmentally based learning strategy for fostering creativity in early childhood education.